(untitled) (Journal of Psychiatrists’ Association of Nepal, 2021)
Koro is a culture bound syndrome exclusive to the South Chinese and Malay Archipelago, although similar cases have been reported outside its boundaries. The hallmark of the classic koro syndrome entails grave fear of penile shrinkage along with its disappearance into the abdomen by retracting inwards and inevitable death upon complete retraction. Absence of this triad of symptoms, or if the syndrome is encountered outside the geographical confines of South-East Asia or China, it is referred to as “koro-like” or “atypical koro”. Here, we report two cases with features of Koro, who presented to the Lagankhel Mental Hospital OPD.